2011
DOI: 10.2196/jmir.1579
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Risk Communication and Planning in an Obese Population: Exploratory Study

Abstract: BackgroundA healthy diet, low in saturated fat and high in fiber, is a popular medical recommendation in preventing cardiovascular disease (CVD). One approach to motivating healthier eating is to raise individuals’ awareness of their CVD risk and then help them form specific plans to change.ObjectivesThe aim was to explore the combined impact of a Web-based CVD risk message and a fully automated planning tool on risk perceptions, intentions, and saturated fat intake changes over 4 weeks.MethodsOf the 1187 men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 48 publications
1
13
1
Order By: Relevance
“…This is of particular interest for younger people where a low absolute 10-year CVD risk can be falsely reassuring [ 37 - 40 ], especially in the presence of multiple raised risk factors. Heart Age was shown to be more likely perceived as a wake-up call among younger (30-45 year old) smokers and/or obese users [ 41 ]. Previous studies also showed that Heart Age motivated people to make healthy behavior changes or had an emotional impact [ 7 , 42 , 43 ], and led to greater reductions in cholesterol, blood pressure, and CVD risk than when a percentage for 10-year CVD risk was provided [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is of particular interest for younger people where a low absolute 10-year CVD risk can be falsely reassuring [ 37 - 40 ], especially in the presence of multiple raised risk factors. Heart Age was shown to be more likely perceived as a wake-up call among younger (30-45 year old) smokers and/or obese users [ 41 ]. Previous studies also showed that Heart Age motivated people to make healthy behavior changes or had an emotional impact [ 7 , 42 , 43 ], and led to greater reductions in cholesterol, blood pressure, and CVD risk than when a percentage for 10-year CVD risk was provided [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Precautionary measures to restrict extreme outcomes of Web-based health assessment tools may generally be useful to limit large inaccuracies in predicted disease risk. Withholding people who have incomplete risk factor information from accessing Web-based self-assessment tools may be a missed opportunity as the Heart Age tool has been shown to motivate women to get their cholesterol tested [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The i f statements are purported to increase the accessibility of critical situations to a person, while the then component of the plan creates a stronger link between the situational cue and the goal-directed response. Promising results of this format have been reported in several health-related behaviors [ 9 - 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies on implementation intentions have used face-to-face communication. These studies showed a reliable effect on diet, physical activity, and smoking cessation [ 5 , 8 - 11 ], whereas evidence from the two studies on the effects of Web-based interventions was mixed [ 12 , 13 ]. In a study conducted in an occupational setting, use of Web-based implementation intentions backfired, such that participants who did not form an implementation intention exercised significantly more than participants who formed an implementation intention [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation